UPAYA PEMERINTAH INDONESIA DALAM MENGHADAPI HEGEMONI CHINA DI KAWASAN LAUT CHINA SELATAN PADA PEMERINTAHAN JOKO WIDODO TAHUN 2016 – 2019 - Harun Umar; Cemara Gita Naya (Jurnal Ilmu dan Budaya, 2020)
China claims Indonesia’s sovereign in Natuna sea, which is located next to South China Sea (SCS). China insists that part of the Natuna sea belongs to China based on Nine-Dash Line map policy which makes it a claim to the South China Sea area. The Nine-Dash Line map was formed based on historical of China’s dynasty. The China’s hegemony is also shown by the islands’ exploration and management in the South China Sea. The conflict between China and Indonesia has been going on for quite a long. It is marked by the China’s actions in sending their fishing vessels to cross the Exclusive Economic Zone (EEZ) and doing the illegal fishing in Natuna sea. There are several confrontation issues between China’s vessel and Indonesia sea in Joko Widodo’s reign, but they are undaunted. They show implicit support to Indonesia’s sovereignty. This research used descriptive method to describe the conflicts in the South China Sea. There were 2 (two) concepts and 1 (one) theory in this research. Those were the Concept of National Interest, the Concept of Sovereignty and Geopolitical Theory. The results of this reasearch showed that the government in Joko Widodo’s reign has attempts in many ways in the face of China’s hegemony that was built in South China Sea, especially in Natuna Sea area. The attempts included the President's assertive demeanor by visiting Natuna, also holding the military training and development. In fact, Indonesia continued its diplomatic attempt in carrying out its role as an honest broker to the South China Sea conflict.